Kiblat dan Perubahan Persepsi Sosial Pasca Gempa Tahun 2004 di Indonesia - Siregar, Muhammad Habibi; Muhammad, Muhammad (Program Studi Pengembangan Masyarakat Islam, 2024)
This study illustrates the reality of differing perceptions within society regarding the direction of the qibla, which has been influenced by the shifting of the Earth caused by several earthquakes that have struck Indonesia. The research employs a phenomenological approach linked to ritual theory, highlighting a strong relationship between spiritual symbols and the behavior of communities who feel connected to these symbols. This situation can also have multiple effects on other fields of study.The researcher found that the emotional attachment of the Muslim community to spiritual symbols, such as mosques, has different implications when faced with the issue of the qibla direction shifting due to recent earthquakes in Indonesia. These implications can be categorized into two aspects: substance and essence.